Adaptação cultural, validade e confiabilidade do Inventário de Habilidades de Vida Independente – versão do paciente (ILSS-BR/P) com portadores de esquizofrenia - Martini, Larissa Campagna [UNIFESP] (2011)
Background: There is a strong association between good psychosocial functioning and the ability to carry out everyday tasks in patients with schizophrenia. Valid Instruments become increasingly necessary to evaluate the performance of these patients on independent living activities. Objective: The aim of this study was to adapt and assess the psychometric properties of the Brazilian version of the Independent Living Skills Survey (ILSS-BR/P) with schizophrenic patients. Method: The study was conducted with three different samples drawn from community mental health services in the city of Sao Paulo. Results: Fifty patients were enrolled in interrater study, with 64.4% agreement between the responses and a range of 0.80-0.99 of the Intraclass Correlation (ICC). Forty-six patients participated in the test-retest, ICC ranged from 0.84-0.94, with 44.3% agreement. There was a good internal consistency. One hundred and sixty patients participated in the validation. In the discriminant validity, female patients presented a higher performance in overall score and five subscales compared with men. The concurrent validity confirmed the specificity of the dimensions of scale, comparing the ILSS with the PANSS, Calgary, CGI, GAF, WHOQOL and the Rosenberg Self-Esteem. Discussion: ILSS-BR/P is a valid and reliable research instrument to assess social functioning of this sample.